Anticancer Effect of Statins in Patients Undergoing Liver Transplantation for Hepatocellular Carcinoma. Issue 3 (29th August 2021) - Lee, Hae Lim; Lee, Sung Won; Jang, Jeong Won; Bae, Si Hyun; Choi, Jong Young; Yoon, Seung Kew; Choi, Ho Joong; Na, Gun Hyung; You, Young Kyoung; Park, Il Young; Kim, Dong Goo
Abstract : The anticancer effect of statins is drawing attention. However, it is unclear whether statin use reduces the risk of hepatocellular carcinoma (HCC) recurrence in patients who undergo liver transplantation (LT) for HCC. Consecutive patients who underwent LT for HCC between 1995 and 2019 were enrolled. The effects of statins on HCC recurrence and mortality were compared between statin user and statin nonuser groups. We performed the analyses in a variety of ways, including inverse probability treatment weighting (IPTW) methods to balance any confounders and the landmark method to avoid immortal time bias. A total of 430 patients were enrolled, among whom 323 (75.1%) were statin nonusers and 107 (24.9%) were statin users. During a median of 64.9 months (IQR, 26.1‐122.6 months) of follow‐up, 79 patients (18.4%) had HCC recurrence and 111 (25.8%) died. Among those who died, 53 (47.7%) were identified as HCC‐related mortalities. Statin use was a predictor of HCC recurrence (adjusted hazard ratio [HR], 0.3; 95% confidence interval [CI], 0.1‐0.6; P = 0.002), all‐cause mortality (adjusted HR, 0.3; 95% CI, 0.2‐0.5; P < 0.001), and HCC‐related mortality (adjusted HR, 0.4; 95% CI, 0.2‐0.9; P = 0.03). The effects of statin use on clinical outcomes were also identified through IPTW analysis. There was a dose‐dependent relationship between statin use and HCC recurrence. The anticancer effect of statins on HCC recurrence was consistently significant across multivariable‐stratified and sensitivity analyses. Statin use significantly reduced the risk of HCC recurrence and improved the survival of patients who underwent LT for HCC.